Thuggery and Cultural Da’wah: A Case Study of Jama’ah Pasrah Foundation, Pati, Indonesia - Hamidulloh Ibda (Jurnal Penelitian, 2019)
This study aims to analyze the model of cultural preaching carried out by Jama'ah Pasrah in reducing thuggery. Through ethnographic and phenomenological research, data were obtained from in-depth interviews with the administrators of Jama'ah Pasrah, the Dukuhseti village community, and ulama. The results of this study revealed that thuggery can be muted through a cultural preaching model, which dialogues culture and Islam Jama'ah Pasrah acculturated through several approaches. The first one was by approaching the thug leaders to participate in tahlilan, zibaan, yasinan, manakiban, and ziarah kubur. Second, providing preaching with nuances of religious art through the establishment of a burdah group. Third, da'wah through tahlilan, yasinan, and manakiban by providing alms or ayam ingkung to eat together. Fourth, giving spiritual guidance through wirid, selawat, hadrah, and also a kind of therapy with recitations of the Holy Qur'an. Fifth, invite ex-thugs to fast for one week with one sahur only. All of those approaches were realized in 12 forms of activities, which were in annual, monthly, and weekly bases. Cultural Da'wah of the Jamaah Pasrah Foundation was able to minimize thuggery from all categories, both Korea, gentlemen and bastard classes.